Performance Model Analysis at the Population and Civil Registration Office of Sarmi Regency, Papua Province - Irfak, Ronaldy; Maya Maria; Amir Fikri (Universitas Trisakti, 2025)
This study analyzes the employee performance model at the Population and Civil Registration Office of Sarmi Regency, Papua Province. Unlike many previous studies that mainly emphasized leadership, discipline, and promotion as direct determinants of performance, this research highlights the psychological and engagement dimensions within a public sector context. Using a quantitative-verificative approach with structural equation modeling, the findings reveal that self-esteem and employee engagement positively influence performance, while job promotion and transformational leadership show no significant effect. These results underscore the importance of strengthening employees’ psychological capital and engagement rather than relying solely on structural or leadership factors. The study contributes to the literature by offering insights into employee performance in a remote bureaucratic setting, while also providing practical implications for human resource management in public institutions.